Radiation activates myeloperoxidase (MPO) to generate active chlorine species (ACS) via a dephosphorylation mechanism - inhibitory effect of LGM2605 - Mishra, Om P.; Popov, Anatoliy V.; Pietrofesa, Ralph A.; Hwang, Wei-Ting; Andrake, Mark; Nakamaru-Ogiso, Eiko; Christofidou-Solomidou, Melpo (Biochimica et biophysica acta. General subjects, 2020)
Radiation exposure of tissues is associated with inflammatory cell influx. Myeloperoxidase (MPO) is an enzyme expressed in granulocytes, such as neutrophils (PMN) and macrophages, responsible for active chlorine species (ACS) generation. The present study aimed to: 1) determine whether exposure to γ-irradiation induces MPO-dependent ACS generation in murine PMN; 2) elucidate the mechanism of radiation-induced ACS generation; and 3) evaluate the effect of the synthetic lignan LGM2605, known for ACS scavenging properties. MPO-dependent ACS generation was determined by using hypochlorite-specific 3′-(p-aminophenyl) fluorescein (APF) and a highly potent MPO inhibitor, 4-aminobenzoic acid hydrazide (ABAH), and confirmed in PMN derived from MPO−/− mice. Radiation-induced MPO activation was determined by EPR spectroscopy and computational analysis identified tyrosine, serine, and threonine residues near MPO's active site. γ-radiation increased MPO-dependent ACS generation dose-dependently in human MPO and in wild-type murine PMN, but not in PMN from MPO−/− mice. LGM2605 decreased radiation-induced, MPO-dependent ACS. Protein tyrosine phosphatase (PTP) and protein serine/threonine phosphatase (PSTP) inhibitors decreased the radiation-induced increase in ACS. Peroxidase cycle results demonstrate that tyrosine phosphorylation blocks MPO Compound I formation by preventing catalysis on H2O2 in the active site of MPO. EPR data demonstrate that γ-radiation increased tyrosyl radical species formation in a dose-dependent manner. We demonstrate that γ-radiation induces MPO-dependent generation of ACS, which is dependent, at least in part, by protein tyrosine and Ser/Thr dephosphorylation and is reduced by LGM2605. This study identified for the first time a novel protein dephosphorylation-dependent mechanism of radiation-induced MPO activation. •LGM2605 inhibits radiation-induced, MPO-dependent ACS generation in MPO and neutrophils.•Radiation-induced ACS generation is, in part, mediated by Tyr and Ser/Thr dephosphorylation.•In non-irradiated cells, MPO activity is dependent on Tyr and Ser/Thr dephosphorylation.•Dephosphorylation is a novel mechanism of radiation-induced, MPO-mediated ACS generation.•LGM2605 is a promising potential attenuator of radiation-induced chlorination damage.